Can the Cambered Bar Enhance Acute Performance in the Bench Press Exercise? - Krzysztofik, Michal; Zajac, Adam; Żmijewski, Piotr; Wilk, Michal (Frontiers in Physiology, 2020)
The main goal of this study was to assess the impact of the cambered bar (CB) during the bench press exercise on power output and bar velocity when compared to a standard bar (SB). Ten healthy strength-trained men (age = 27.9 ± 3.7 years; body mass = 90.1 ± 12.5 kg; resistance training experience = 6.5 ± 2.7 years; bench press one-repetition maximum (1RM) = 118.5 ± 21 kg) performed a single set of 3 repetitions of the bench press exercise with an SB and a CB at 50%1RM to assess differences in peak power output (PP), mean power output (MP), peak bar velocity (PV), and mean bar velocity (MV), range of motion (ROM), and positive work time under load (TUL) between conditions. The t-test indicated significantly higher mean ROM for the cambered bar in comparison to the standard bar (52.7 vs. 44.9 cm; P < 0.01; ES = 1.40). Further, there was a significantly higher PP (907 vs. 817 W; P < 0.01; ES = 0.35), MP (556 vs. 496 W; P < 0.01; ES = 0.46), PV (1.24 vs. 1.14 m/s; P < 0.01; ES = 0.35) and MV (0.89 vs. 0.82 m/s; P < 0.01; ES = 0.34) for the CB condition when compared to the SB. A significantly longer TUL for the CB was observed, when compared to the SB (1.89 vs. 1.51 s; P < 0.01; ES = 1.38). The results of this study showed that the CB significantly increased power output and bar velocity in the bench press exercise at 50%1RM compared to the SB. Therefore, the additional ROM, made possible through the use of the CB, allows for the acceleration of the bar through a significantly longer displacement, which has a positive impact on power output. However, a simultaneous increase in TUL may cause higher fatigue when the bench press is performed with the CB compared to the SB.